Effects of digitonin on hyperglycaemia and dyslipidemia induced by high-sucrose intake - Ebaid, GMX; Faine, L. A.; Diniz, Y. S.; Rodrigues, H. G.; Galhardi, C. M.; Ribas, B. O.; Fernandes, AAH; Novelli, ELB (Elsevier B.V., 2006)
This study examined whether high-sucrose intake effects on lipid profile and oral glucose tolerance may be inhibited by a single administration of digitonin, a saponin from the seeds of Digitalis purpurea Male Wistar 24 rats were initially divided into two groups (n = 12): (C) was given standard chow and water; (S) received standard chow and 30% sucrose in its drinking water. After 30 days of treatments, C rats were divided into two groups (n = 6): (CC) given an intra-gastric dose 0.5 mL saline, (CD) given a single intragastric dose of 15 mg/kg digitonin. S rats were also divided into two groups (n = 6): (SC) given intra-gastric saline and (SD) given digitonin. Rats were sacrificed after the oral glucose tolerance test (OGTT) at 2 h after the digitonin administration. S rats had higher total energy intake and final body weight than C. SC rats had fasting hyperglycaemia and impaired OGTT. Digitonin in SD group improved the glucose tolerance. Triacylglycerol (TG), very-low-density lipoprotein (VLDL-C) and free fatty acid (FFA) serum concentrations were increased in SD rats from CC. Digitonin in SD rats decreased FFA and led TG and VLDL-C concentrations at the levels observed in the CC group. Despite the enhanced cholesterol in CD group from CC., the high-density lipoprotein (HDL-C) was increased in these animals. HDL-C/TG ratio was higher in CD and SD than in CC and SC, respectively. No significant differences were observed in lipid hydroperoxide(LH) between the groups. VLDL-C/LH ratio and gamma-glutamyl transferase (GGT) activity were increased in SC group and were decreased in SD rats from the SC. In conclusion digitonin enhanced glucose tolerance and had beneficial effects on serum lipids by improve antioxidant activity. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: digitonin; sucrose; glucose tolerance; lipid profile; oxidative stress; obesity